Assessment of Fine Motor Development in Early Childhood at TKIT Ar-Rahmah - Iqlima Fitria Ningsih (LP3M STAI MA'ARIF MAGETAN, 2024)
This study aims to analyze, describe an assessment or assessment of fine motor development in early childhood at IT Ar-Rahmah Kindergarten, Bener Meriah Regency. The subjects in this study were 15 B grade children, 2 teachers and 1 school principal. The research technique uses descriptive qualitative, while the data analysis technique uses observation and interviews, data collection techniques in the form of anecdotal notes, work and portfolios. In research at the IT Ar-Rahmah Kindergarten, the three assessment techniques were used to describe aspects of child development which were arranged in the form of documents and portfolios, teachers also used cameras to photograph and print children's work, and used videos for anecdotal notes. The work done by the child may be brought home to be shown to the parents, then apart from the teacher, the parents can also evaluate the child's fine motor development with the work that is brought. For the final results of the semester, the teacher prepares three forms of assessment, but in TK IT Ar-Rahmah the teacher tends to prefer the assessment in the form of a checklist, namely BB, MB, BSH, BSB as well as giving an assessment in the form of a star symbol. In addition to the three techniques above, the researcher describes several assessment techniques that can be used by teachers such as test and non-test instruments.